PENGEMBANGAN E-MODUL IPAS BERBASIS PROBLEM BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA SD - Asri, Kanthi; Haryani, Sri; Ellianawati, Ellianawati; Bambang Subali; Nuni Widiarti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The increasingly advanced education world in alignment with technology is very necessary. In fact, the ability of teachers to develop technology-based learning media to enhance students' thinking skills is still limited. This research aims to determine the feasibility and effectiveness of a Problem Based Learning (PBL) e-Module in improving the critical thinking skills of elementary school students in Kramat District, Tegal Regency. The research method applied is the Four D (4D) development model: Define, Design, Develop, and Disseminate. Research data were obtained from observations, interviews, questionnaires, tests, and documentation. Based on the validator team's assessment, the material aspect was rated at 92%, indicating that the Problem Based Learning e-Module is very feasible for use by students. Based on the N-Gain Score results, the experimental class achieved an average of 0.72, which is categorized as high, while the control class achieved an average of 0.45, which is categorized as medium. Thus, it can be concluded that the Problem Based Learning e-Module is feasible and effective in improving the critical thinking skills of elementary school students.